2010
DOI: 10.1111/j.1365-2311.2009.01168.x
|View full text |Cite
|
Sign up to set email alerts
|

Being a generalist herbivore in a diverse world: how do diets from different grasslands influence food plant selection and fitness of the grasshopper Chorthippus parallelus?

Abstract: 1. Generalist insect herbivores occupy a variety of habitats that differ in food plant composition. Dietary mixing has been proposed as a possibility for generalists to overcome nutritional deficiencies of single plant species, but only a few studies have investigated herbivore feeding and fitness for diets that resemble natural scenarios. We studied feeding behaviour, survival, and reproduction of the generalist grasshopper Chorthippus parallelus raised on food plants of four typical habitats. 2. Grasshopper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 43 publications
1
42
0
Order By: Relevance
“…Furthermore, polyphagy will be favoured by migratory species, since different suites of host plants are likely to be encountered in different locations (Michaud, 1990). Diet-mixing is also predicted under the physiological-efficiency hypothesis to reduce the build up of defensive chemicals and counteract nutritional deficiencies that may arise from single-host diets (Held & Potter, 2004;Franzke et al, 2010;Karban et al, 2010). However, DNA barcoding has shown that some widespread, generalist species are actually complexes of multiple closely related host-specific species (Hebert et al, 2004;Janzen et al, 2009Janzen et al, , 2012Valentini, Pompanon & Taberlet, 2009; but see Hulcr et al, 2007a).…”
Section: Host Specialisationmentioning
confidence: 97%
“…Furthermore, polyphagy will be favoured by migratory species, since different suites of host plants are likely to be encountered in different locations (Michaud, 1990). Diet-mixing is also predicted under the physiological-efficiency hypothesis to reduce the build up of defensive chemicals and counteract nutritional deficiencies that may arise from single-host diets (Held & Potter, 2004;Franzke et al, 2010;Karban et al, 2010). However, DNA barcoding has shown that some widespread, generalist species are actually complexes of multiple closely related host-specific species (Hebert et al, 2004;Janzen et al, 2009Janzen et al, , 2012Valentini, Pompanon & Taberlet, 2009; but see Hulcr et al, 2007a).…”
Section: Host Specialisationmentioning
confidence: 97%
“…Changes in diet across a species’ range have been observed in other grasshopper species (Franzke et al. 2010). Additionally, DNA analysis of diet cannot reflect diet over a large temporal scale as it is limited by the transit time of food through the digestive tract of grasshoppers – estimated at 6 h (Chapco and Kelln 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The meadow was dominated by grasses, namely Poa pratensis, Dactylis glomerata , Festuca pratensis , and Bromus sterilis , which are all potential food plants for the generalist herbivores in grasslands [1], [2], [3], [4]. Three days before the start of the experiment, we caught female and male grasshoppers with sweep nets and kept them separately in cages with a mixed grass diet from the meadow until the start of the experiment.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%